3102-2024 - IEEE Standard for Conservation Voltage Reduction (CVR) Data Collection and Management Procedures (IEEE, 2025)
Challenges in conducting measurement and verification in conservation voltage reduction (CVR) deployed feeders are faced by utilities. A standard is needed to provide procedures for electric utilities to determine the energy savings and CVR factors of their CVR programs, to define parameters for regulatory reporting, and to define standardized verification methodology selection based on standard data collection methodologies. The specification of CVR data management and collection procedures for use by the electric utility industry to enable energy savings is the purpose of this standard. Electric utilities, electric utility equipment manufacturers, software vendors, and electric utility regulatory commissions are the included stakeholders for this standard.
Keywords: Energy consumption.